2017
DOI: 10.1097/iop.0000000000000603
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-131 Therapy and Lacrimal Drainage System Toxicity: Nasal Localization Studies Using Whole Body Nuclear Scintigraphy and SPECT-CT

Abstract: Intranasal localization of radioactive I-131 was significant in patients receiving a dose of ≥150 mCi. Intranasal localization may partly explain toxicity to nasolacrimal duct and may be a risk factor for subsequent development of nasolacrimal duct obstructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
(35 reference statements)
0
7
0
6
Order By: Relevance
“…Besides thyroid tissue itself, sweat and salivary glands and the nasal cavity also have the ability to uptake and store iodine through their sodium iodide transporters. Body uids such as gastric juice, cerebrospinal uid, breast milk and fetal blood can also incorporate 131 I [14] leading to an impact of 131 I therapy for DTC on gonadal function and reproductive health. As a result, the effects of 131 I therapy have attracted a great deal of attention [5] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides thyroid tissue itself, sweat and salivary glands and the nasal cavity also have the ability to uptake and store iodine through their sodium iodide transporters. Body uids such as gastric juice, cerebrospinal uid, breast milk and fetal blood can also incorporate 131 I [14] leading to an impact of 131 I therapy for DTC on gonadal function and reproductive health. As a result, the effects of 131 I therapy have attracted a great deal of attention [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen cases had unilateral or bilateral stenosis with lacrimal drainage system obstruction con rmed by ophthalmologists. Ali MJ et al [14] found that no patient receiving 3.7 GBq had symptoms but 4% (2 / 50) of patients receiving more than 5.55 GBq did. High dose 131 I is therefore associated with nasolacrimal duct obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…RAI is excreted in tears and actively accumulated in LDS and subsequently lacrimal gland impairment [35] as well as epiphora can develop since the low, but concentrated level of RAI induces inflammation that stimulates stenosis or obstruction [36]. Investigating RAI administration in a high number of patients, a cutoff level of 150 mCi was determined since toxicity and consecutive inflammation that leads to obstruction of LDS occurred in patients who received RAI doses above this level [37].…”
Section: Discussionmentioning
confidence: 99%
“…и M. Ali и cоавт. [10][11][12] с помощью однофотонной эмиссионной компьютерной томографии (ОФЭКТ) выявили накопление радиоактивного йода в тканях носослезного протока у пациентов после терапии радиоактивным йодом. Эти данные позволяют считать поражение слезоотводящих путей специфическим осложнением терапии радиоактивным йодом.…”
unclassified
“…M. Ali и соавт. [12] показали, что нарушения слезоотведения зависят от дозы радиоактивного йода. С помощью ОФЭКТ накопление радиоактивного йода в области носовой полости и носослезного протока было выявлено у пациентов, получавших терапию радиоактивным йодом в дозе 100 мКи (50 наблюдений) и более 150 мКи (50 наблюдений).…”
unclassified